2020
DOI: 10.1136/bmjopen-2019-032435
|View full text |Cite
|
Sign up to set email alerts
|

Global estimate of the prevalence of post-traumatic stress disorder among adults living with HIV: a systematic review and meta-analysis

Abstract: ObjectivesAlthough people living with HIV (PLWH) have been disproportionately affected by post-traumatic stress disorder (PTSD), the global prevalence of PTSD among PLWH is unknown. This study aimed to systematically review the prevalence of PTSD among PLWH worldwide and explore variation in prevalence across sociodemographic and methodological factors.DesignA meta-analysis using a random-effects model was conducted to pool the prevalence estimated from individual studies, and subgroup analyses were used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 86 publications
3
39
1
Order By: Relevance
“…Participants with a history of traumatic events were most likely to experience the negative impact of COVID-19 prevention measures and more likely to have comorbid disorders associated with an increased risk of severe COVID-19. Previous studies have illustrated greater prevalence of trauma among PWH 39 42 and have highlighted the far-reaching consequences of trauma on overall health. 43 , 44 Expanding training and capacity in trauma aware care for HIV care providers, especially through virtual platforms, may be a useful strategy for better health outcomes for affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Participants with a history of traumatic events were most likely to experience the negative impact of COVID-19 prevention measures and more likely to have comorbid disorders associated with an increased risk of severe COVID-19. Previous studies have illustrated greater prevalence of trauma among PWH 39 42 and have highlighted the far-reaching consequences of trauma on overall health. 43 , 44 Expanding training and capacity in trauma aware care for HIV care providers, especially through virtual platforms, may be a useful strategy for better health outcomes for affected individuals.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Traumatic stress occurs in 9% to 27% of patients who experience an acute medical event. Medical PTS is most often explored among patients with cancers, 6 , 7 cardiovascular disease, 8 , 9 and HIV/AIDS, 10 , 11 with multiple studies showing persistent trauma symptoms. Because patients with severe inflammatory bowel disease (IBD) often have repeated emergency department visits and emergency surgeries and may utilize treatments with rare but serious adverse effects, it is possible that a proportion of these patients will develop PTS.…”
Section: Introductionmentioning
confidence: 99%
“…The present meta-analysis of 12 studies found that there was elevated odds of ART non-adherence amongst HIV-infected participants with PTSD. Although the effect size for this association was small, from the perspective of public health, the result is still meaningful in making public health policy in terms of high prevalence (28%) of PTSD among PLWH worldwide ( 5 ). Moreover, there was a significant effect toward this association among younger participants and depression-unadjusted studies.…”
Section: Discussionmentioning
confidence: 92%
“…Compared with the general population, posttraumatic stress disorder (PTSD) is a commonly reported psychiatric disease among people living with HIV (PLWH) (1)(2)(3)(4). The estimated prevalence of PTSD in PLWH was 28% worldwide, and PTSD is a frequent encountered psychiatric comorbidity in HIV primary care setting (5). PLWH with PTSD symptoms may be tremendously affected by unaffordable public health cost, disabling psychological distress, worsened quality of life, and even increased odds of suicide (6,7).…”
Section: Introductionmentioning
confidence: 99%